Kinetic and structural features of furan compounds as inhibitors of the radical polymerization of vinyl acetate - Rebeca Vega; Jacques Rieumont (Polímeros, 1997)
Some furan compounds bearing a double bond in the side group have been examined as inhibitors of the radical polymerization of vinyl acetate initiated by AIBN in ethyl acetate at 60 ºC. The inhibition effect was found to follow the order: furfurylidenacetone > furylacrolein > furanacrylic acid > furylacrylmorpholinamide as a consequence of the greater stabilization of the radical formed. The site of radical attack can be considered either as the C-5 position of the furan ring or as the double bond of the side group. The compounds taken as models such as 5-methylfuranacrylic acid and furfurylidenbutanal indicate that both positions can participate in the inhibitory process.